2019
DOI: 10.3390/s19245472
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Enhancing Microwave Brain Imaging Using Metamaterials

Abstract: We present an approach to enhance microwave brain imaging with an innovative metamaterial (MM) planar design based on a cross-shaped split-ring resonator (SRR-CS). The proposed metasurface is incorporated in different setups, and its interaction with EM waves is studied both experimentally and by using CST Microwave Studio® and is compared to a “no MM” case scenario. We show that the MM can enhance the penetration of the transmitted signals into the human head when placed in contact with skin tissue, acting as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…The metallic pattern (thickness = 0.10 mm) is a variation of the Jerusalem Cross SRR. Our previous studies have already shown the MM unit cell design and the performance of MM layers based on this structure [13], [14].…”
Section: B Simulation Setupmentioning
confidence: 93%
“…The metallic pattern (thickness = 0.10 mm) is a variation of the Jerusalem Cross SRR. Our previous studies have already shown the MM unit cell design and the performance of MM layers based on this structure [13], [14].…”
Section: B Simulation Setupmentioning
confidence: 93%
“…These two high dielectric substrates are bonded with with Rogers 3001 bonding film ( = 2.28, tan = 0.003). In previous work [ 18 , 34 ], we have performed several simulation studies to optimize this geometry for operating in contact with the human skin when immersed in our coupling medium.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…To test the performance of our new PSMA and MTS-enhanced PSMA operating in air, we compared our previous developed brain scanner operating in an infinite lossy matching medium to two tomographic systems: an 8-PSMA system and an 8-MTS-enhanced PSMA system. Our previous developed MWT scanner for brain imaging consists of 12 spear patch antennas immersed in a 90% glycerol-water mixture and placed around EN 50361 Specific Anthropomorphic Mannequin (SAM) head model [ 18 , 19 ]. A similar setup (“System 1”), including 8 antennas placed elliptically around our numerical head model, was modelled in CST Microwave Studio.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MM structures can be used to couple the incident power into the brain tissue. To this end, our previous studies have shown that tailored MM designs might be a powerful advance towards the development of MWT scanners [6]. This paper examines the potential of improving the quality of the reconstructed images by integrating MM technology in our radar-based imaging scanner.…”
Section: Introductionmentioning
confidence: 99%